Fuṣūṣ al-ḥikam and the philosophycal challenges of a visionary book - Diego González, Antonio de (2024)
Fuṣūṣ al-ḥikam is one of the most important works of the Andalusian mystic and thinker Muḥyī l-dīn Ibn ‘Arabī (1165-1240). This text, one of the most beautiful examples of medieval thought, constitutes an authentic symbolic repository of the knowledge of the Abrahamic tradition. At the same time, the Murcian master attributes this work to a visionary experience in the form of descended knowledge of which he felt himself to be a mere transcriber. This paper proposes to analyze symbolically the challenges of a visionary book and, on the other hand, the resources it uses: the prophets as archetypes to justify the transcendental anthropology of the perfect human being (al-insān al-kāmil) and the methodology of the “strung chain” to legitimize a knowledge beyond reason.